Analisa Persepsi dan Preferensi Kualitas Buah Tropis - Wibowo, Dick Felixs; Palit, Herry Christian (Jurnal Titra, 2013)
This research are to find out how the preferences and perceptions of Surabaya people againts the national tropical fruits and import fruits based on their economic levels and type of fruits that they purchased. Data that got from questionnaire is tested validation and reliability. And then, the analysis continued with Kruskal-Wallis test and Factor Analysis. The result of this research is Surabaya people prefer to buy import fruits than national tropical fruits. Surabaya people perception of the national tropical fruits and import fruits vary by the level of economy and the type of fruits purchased.